2002
DOI: 10.1046/j.1468-1331.2002.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between seropositivity to Chlamydia pneumoniae and acute ischaemic stroke

Abstract: Recent studies suggest an association between Chlamydia pneumoniae infection with atherosclerosis, including cerebrovascular disease. We investigated the prevalence of Chlamydial seropositivity in patients with acute ischaemic stroke syndrome compared with age- and sex-matched control subjects. Specific antibodies (IgA) to C. pneumoniae were measured by microimmunofluorescence in both the clinical group (n=91) and the control group (n=112). Forty patients (43.9%) and 34 controls (30.3%) had positive IgA titres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…Many case-control studies 8,9,12,13,25,26 have demonstrated an association between antibodies against C pneumoniae (mainly IgA) and stroke in other populations. Some seroepidemiological studies have also reported an association between past C pneumoniae infection and asymptomatic carotid atherosclerosis, [27][28][29][30] although this finding has not been consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Many case-control studies 8,9,12,13,25,26 have demonstrated an association between antibodies against C pneumoniae (mainly IgA) and stroke in other populations. Some seroepidemiological studies have also reported an association between past C pneumoniae infection and asymptomatic carotid atherosclerosis, [27][28][29][30] although this finding has not been consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of the vascular wall with Cp has been linked to ischemic heart disease (2-5) and stroke (6)(7)(8)(9)(10)(11)(12) in epidemiological studies and in pathological studies using immunocytochemistry, polymerase chain reaction (PCR) and electron microscopy. In Japan, Miyashita et al (13) reported a significant elevation of Cp antibody level in an acute myocardial infarction patient and Kawamotoet al (14) showed a significant relation between atherosclerotic lesions and common carotid arteries.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective and cross-sectional studies have suggested that both bacterial and viral infections may be risk factors for atherosclerosis, ischemic stroke and acute coronary events (7)(8)(9)(10)(11). Some studies do not confirm the association between seropositivity to C. pneumoniae and increased risk of cardiovascular diseases in populations with stroke (12). Although, the role of C. pneumoniae infection has been seriously considered in patients with myocardial infarction as a new atherothrombotic risk factor, but in acute ischemic stroke there are few data to support the eventual association (13).…”
Section: Introductionmentioning
confidence: 99%